Problems and Reorientation of Da’wah: Analysis of Social Construction in the Metaverse Era - Effendi, Dudy Imanuddin; Mareta, Mira; Sarbini, Ahmad (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
The purpose of this study is expected to reveal social phenomena that emerge, such as the construction of social interactions, social changes, and emerging societal models in the metaverse era. This examination employs a critical method aimed at uncovering, explaining, and critiquing narratives about the social conditions occurring in metaverse-era society. Additionally, this investigation utilizes a virtual ethnography approach to understand and explain various depictions and consequences on the complex social world in the metaverse era, whether informed structurally or culturally through technological media. The hope is that the output of this study can map out the issues of da’wah with various detrimental social consequences resulting from technological disruption in the metaverse era. Similarly, the results of this study are expected to serve as an academic reference in formulating preaching policies in the metaverse era. This study has demonstrated the historical development of the interpretation of the term metaverse, the influence of technological schemes that have constructed social interactions, the character of dystopian society as a da’wah problem, and also the orientation of da’wah that must be designed to address social changes in the metaverse era.